Bioactive Compounds and Functional Properties of Herbal Preparations of Cystus creticus L. Collected From Rhodes Island - Mocan, Andrei; Fernandes, Ângela; Calhelha, Ricardo C.; Gavrilaş, Laura; Ferreira, Isabel C. F. R.; Ivanov, Marija; Sokovic, Marina; Barros, Lillian; Babotă, Mihai (Frontiers in Nutrition, 2022)
The members of Cystus genus are perenial shrubs with a well-established use in traditional medicine. Among these, C. creticus is the most popular, herbal preparations obtained from its aerial parts being recognized as antimicrobial, antitumor and anti-inflammatory agents. The present study aimed to evaluate phytochemical profile and bioactive potential of aqueous and hydroethanolic extracts of C. creticus aerial parts harvested from two different areas of Rhodes island. LC-DAD-ESI/MSn analysis revealed the presence of myricetin and quercetin glycosides as main compounds, especially in aqueous extracts, being probably responsible for their enhanced antioxidant and antimicrobial potential. On the other side, hydroethanolic preparations exerted a strong anti-inflammatory and anti-biofilm activity. Our findings suggest that the use of solvents with intermediate polarity can assure the best recovery of bioactive compounds from C. creticus, increasing the extraction yield for other non-phenolic compounds which can enhance therapeutic potential of the extract through a synergistic action.